Editorial: The power of collaboration - Kate Sanders (Foundation of Nursing Studies, 2021)
Since Covid-19 appeared almost two years ago, strategic leaders and academics have offered their wisdom to leaders ‘in the field’ in terms of what worked for them during previous crises. Learning from others’ experiences may be helpful, but the unprecedented nature of the context in which we are living and working has called for innovation, creativity and collaboration, to ‘work things out’. A theme of positivity runs through literature, encouraging leaders to foster hope through being available, listening, responding and showing compassion at a time when there seemed little reason to be positive. Over the difficult period of the pandemic, though, there have been so many stories of close collaborations, person-centred ways of being, helpfulness and kindness, and collaboration is a central theme in this issue of the IPDJ.